Transcranial Magnetic Resonance-Guided Focused Ultrasound Thalamotomy in Essential Tremor: A Comprehensive Lesion Characterization. Issue 2 (1st October 2019) - Pineda-Pardo, José Angel; Urso, Daniele; Martínez-Fernández, Raul; Rodríguez-Rojas, Rafael; del-Alamo, Marta; Millar Vernetti, Patricio; Máñez-Miró, Jorge U; Hernández-Fernández, Frida; de Luis-Pastor, Esther; Vela-Desojo, Lydia; Obeso, José A
Abstract: BACKGROUND: Transcranial magnetic resonance-guided focused ultrasound (tcMRgFUS) thalamotomy is a novel and effective treatment for controlling tremor in essential tremor patients. OBJECTIVE: To provide a comprehensive characterization of the radiological, topographical, and volumetric aspects of the tcMRgFUS thalamic lesion, and to quantify how they relate to the clinical outcomes. METHODS: In this study, clinical and radiological data from forty patients with medically-refractory essential tremor treated with unilateral tcMRgFUS thalamotomy were retrospectively analyzed. Treatment efficacy was assessed with Clinical Rating Scale for Tremor (CRST). Lesions were manually segmented on T1, T2, and susceptibility-weighted images, and 3-dimensional topographical analysis was then carried out. Statistical comparisons were performed using nonparametric statistics. RESULTS: The greatest clinical improvement was correlated with a more inferior and posterior lesion, a bigger lesion volume, and percentage of the ventral intermediate nucleus covered by the lesion; whereas, the largest lesions accounted for the occurrence of gait imbalance. Furthermore, the volume of the lesion was significantly predicted by the number of sonications surpassing 52°C. CONCLUSION: Here we provide a comprehensive characterization of the thalamic tcMRgFUS lesion including radiological and topographical analysis. Our results indicate that the location and volume of the lesion were significantly associated with the clinical outcome and that mid-temperatures may be responsible for the lesion size. This could serve ultimately to improve targeting and judgment and to optimize clinical outcome of tcMRgFUS thalamotomy.